2014
DOI: 10.6061/clinics/2014(12)01
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and iron content evolution in exclusively breastfed late-preterm newborns

Abstract: OBJECTIVES:To analyze and compare the evolution of hematological parameters and body iron content between exclusively breastfed late-preterm and term newborns during the first two months of life.METHODS:Cohort study. Weight, length, head circumference, body mass index, hemoglobin, hematocrit, reticulocytes, total iron-binding capacity, transferrin saturation, serum iron and ferritin were measured in 25 late-preterm and 21 term newborns (at birth and at one and two months of age) who were exclusively breastfed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…Studies of over 40,000 term and preterm infants in the United States have shown that mean Hb decreases from about 180 g/L at birth to ∼120−130 g/L at 1 month, and then to just over 110 g/L at 3 months . Similar decreases in mean Hb have been seen among Brazilian infants ( n = 46), from 160 g/L at birth to 120 g/L at 1 month to 110 g/L at 2 months . Among infants in the Gambia ( n = 675), Hb declined significantly with increasing age from 2 to 10 months (estimated 2.5th and 97.5th percentiles for infants 2−5 months: 90−127 g/L for males and 93−129 g/L for females; and 6−10 months: 82−123 g/L for males and 86−126 g/L for females) .…”
Section: Variation In Average Hb Values Across Life Stages and By Sexsupporting
confidence: 52%
“…Studies of over 40,000 term and preterm infants in the United States have shown that mean Hb decreases from about 180 g/L at birth to ∼120−130 g/L at 1 month, and then to just over 110 g/L at 3 months . Similar decreases in mean Hb have been seen among Brazilian infants ( n = 46), from 160 g/L at birth to 120 g/L at 1 month to 110 g/L at 2 months . Among infants in the Gambia ( n = 675), Hb declined significantly with increasing age from 2 to 10 months (estimated 2.5th and 97.5th percentiles for infants 2−5 months: 90−127 g/L for males and 93−129 g/L for females; and 6−10 months: 82−123 g/L for males and 86−126 g/L for females) .…”
Section: Variation In Average Hb Values Across Life Stages and By Sexsupporting
confidence: 52%
“…Micronutrient stores in preemies are rapidly depleted in the first weeks after birth, and their fast growth rate is associated with higher micronutrient requirements 7 , 30 , 31 . Yamada et al 32 compared late preemies with term infants and found lower Hb levels and iron stores in preemies one month after birth, which reinforces the need for iron supplementation in this population. Fares et al 33 found a high incidence of vitamin A deficiency (75.9%) in very low birth weight preemies.…”
Section: Discussionmentioning
confidence: 92%
“…48 c. Breastfed late preterm infants are at increased risk for iron deficiency and iron deficiency anemia compared with term infants, and routine iron supplementation is recommended. [54][55][56] (lV, lll, and lB) d. Late preterm infants are also more likely to sleep in unsafe situations as compared with term infants, 57 thus adding to the established increased risk of sudden infant death syndrome (SIDS) in preterm infants. Therefore, regular inquiry into sleep position and location is also warranted.…”
Section: (Llb)mentioning
confidence: 99%